Answer:
x = -4
y = -3
Explanation:
to solve the system of linear equation we say that let
6x - 2y = -18........................ equation 1
2x - 2y = -2.......................... equation 2
from equation 2
2x - 2y = -2.......................... equation 2
2x = -2 + 2y
divide both sides by 2
2x/2 = ( -2 + 2y)/2
x = ( -2 + 2y)/2................................ equation 3
substitute for x in equation 1
6x - 2y = -18........................ equation 1
6[( -2 + 2y)/2] - 2y = -18
-6 + 6y- 2y = -18
collect the like terms
6y - 2y = -18 + 6
4y = -12
divide both sides by the coefficient of y which is 4
4y/4 = -12/4
y = -3
put y = -3 in equation 3
x = ( -2 + 2y)/2................................ equation 3
x = -2 + 2(-3)/2
x = -2-6/2
x = -8/2
x = -4
therefore the value of x and y in the equation is -4 and -3 respectively.